Moderne Spiele: Play and Gender in Walter Benjamin’s “Berlin Chronicle” (Konturen, 2019)
This essay performs a reading of Walter Benjamin’s “Berlin Chronicle” to show that what is at stake in this work is the question of male sovereignty as it relates to the modern city and the modernist text as spaces of play. This autobiographical sketch draws and, in its form, explores an analogy between the ways city spaces are organized and the way writing organizes a life’s memories into spatially distributed groupings of signs. Its fragmentary, reflexive structure purports to challenge the linearity of standard autobiographical writing, subjecting them to the play of associations and the casual stroll of the flâneur. Given Benjamin’s emphasis, here as well as elsewhere, on a method of composition that reflects the “surface play” of 20th-century modernity, it would seem that the reader is also invited to stroll like the flâneur, or play like the gambler, through the text. The city and the essay become analogous to each other as spatial constructs the reader is invited to circumnavigate—they create Spielraum, or room-for-play. However, Benjamin’s game is deceptive, as he strategically entraps the feminine—represented by the rather Oedipal coupling of Benjamin’s mother and a variety of lovers and prostitutes—within this space. On a closer reading, gendered difference becomes the protocol by which a textual-urban network operates in “Berlin Chronicle,” making it exemplary of the ways in which playful modern media and spaces condition and position subjects within their games.